Clinical impact of c-KIT and CEBPA mutations in 33 patients with corebinding factor (Non-M3) acute myeloid leukemia - Xiaoyan Mao; Runxiu Yin; Li Liu; Yan Zhou; Chunhui Yang; Chunlian Fang; Hongchao Jiang; Qulian Guo; Xin Tian (Pediatrics and Neonatology)
Background: Corebinding factor acute myeloid leukemia (CBF-AML) is the most common cytogenetic subtype of pediatric AML. CBF-AML is associated with a relatively favorable outcome, although the relapse rate of approximately 40% indicates a high degree of clinical heterogeneity. The clinical impact of additional cytogenetic aberrations, including c-KIT and CEBPA mutations, in pediatric CBF-AML has not been well characterized, especially in the multi-ethnic region of Yunnan Province in China. Methods: In this study, we retrospectively analyzed the clinical features, gene mutations, and prognoses of 72 pediatric patients newly diagnosed with non-M3 AML in Kunming Children's Hospital, China, from January 1, 2015 to May 31, 2020. Results: Of the 72 pediatric patients with AML, 46% (33/72) had CBF-AML. Thirteen patients with CBF-AML (39%) had c-KIT mutations, five (15%) had CEBPA mutations, and eleven (33.3%) had no other cytogenetic aberrations. The c-KIT mutations, resulting from single nucleotide substitutions and small insertions or deletions, occurred in exons 8 and 17. All of the CBF-AML-associated CEBPA mutations were single mutations and occurred in patients with RUNX1-RUNX1T1 fusion. We found no significant differences in the clinical data between CBF-AML patients with c-KIT or CEBPA mutations and CBF-AML patients without other aberrations, and no prognostic significance was established for these mutations. Conclusion: Our study is the first to report the clinical impact of c-KIT and CEBPA mutations in pediatric patients with non-M3 CBF-AML from the multi-ethnic Yunnan Province, China. c-KIT and CEBPA mutations occurred at a higher frequency in CBF-AML cases and were associated with unique clinical characteristics; however, no potential molecular prognostic markers were identified.